Prototype Development of Interactive Multimedia Manual and Electronic Recordkeeping Simulator for E-Archive Learning - Novi Ashari, T; Pramusinto, H (KnE Social Sciences, 2018)
The research aims to develop web-based interactive multimedia Manual and Electronic Recordkeeping Simulator (M.E.R.S.) that proper to be applied as a medium of electronic archives learning for office administration program in vocational schools. The kind of this study is research and development (R&D). The design of the research is involves identification of the potential and problems, data collection, making of design, design validation, prototype design revision, and products trials. M.E.R.S. was developed by using web technology that have many advantages so it can be more accessible. The results of this study shows that M.E.R.S. considered very feasible with a mean percentage of 90%. Material expert is scoring 38 out of 40 with a percentage of 95% (criterion very decent) while the media experts provides an assessment score of 34 out of 40 with a percentage of 85% (criterion very decent). M.E.R.S. also effective in increasing students positive perception, motivation, and understanding about electronic archival learning practice. Based on the results, it can be concluded that medium successfully developed by using R&D research approach. M.E.R.S. also considered feasible by the material expert and media expert as a medium for learning which it can be applied in the electronic archive learning for office administarion program. Even so, M.E.R.S. still needs to be extensively tested through further research to get another effectiveness so that it can be improved. Keywords: medium, multimedia, simulator, electronic record, e-archive learning